Rates of Return to Sport After Surgical Management of Multiligament Knee Injuries Are Higher Than Previously Described yet Highly Heterogeneous: A Systematic Review - Dworsky-Fried, Joshua; Kotipalli, Satyavenkata; Vivekanantha, Prushoth; Alomari, Meshal; Tapasvi, Sachin; Moatshe, Gilbert; Martin, Ryan; de Sa, Darren (Arthroscopy, 2025)
To provide an updated overview of return to sport (RTS) and return to work (RTW) after surgical management of multiligament knee injuries (MLKIs). A search was conducted across the MEDLINE, Embase, and PubMed databases from inception to August 26, 2024. Studies published after 2018 that reported on rates of RTS or RTW after multiligament knee reconstruction were included. Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines were followed, and a quality assessment was performed using the Methodological Index for Non-randomized Studies (MINORS) criteria. Data on study characteristics, demographic characteristics, and surgical details were extracted. Rates of RTS or RTW at the same level or at any level of participation were recorded. Random-effects models were used to generate forest plots. Fifteen studies reported on RTS, with rates ranging from 41.2% to 100% when investigating RTS at any level. Thirteen studies reported rates of return to preinjury level, ranging from 5.9% to 100%. RTS rates at any level and preinjury level had higher ceilings than shown in a prior systematic review. Time taken to RTS ranged from 6.7 to 24.9 months. Twelve studies reported on RTW at any capacity, with rates ranging from 41% to 100%. Seven studies reported rates of RTW at preinjury capacity, ranging from 39.3% to 100%. For both RTS and RTW outcomes, high heterogeneities precluded pooled estimates. Time taken to RTW ranged from 2.4 to 24.8 months. Substantially lower RTW rates were associated with multi-trauma dislocations and sedentary occupations. Rates of RTS at any level and preinjury level ranged from 41.2% to 100% and 5.9% to 100%, respectively, with corresponding heterogeneity values of 91% and 83%. These rates have higher ceilings than reported in a previous systematic review. Currently, there is insufficient evidence to recommend one surgical approach over another. Level IV, systematic review of Level III and IV studies.